First Case of Human Ocular Dirofilariasis in the Aosta Valley Region: Clinical Management and Morphological-Molecular Confirmation - Erik Mus; Annalisa Viani; Lorenzo Domenis; Fabio Maradei; Antonio Valastro; Gianluca Marucci; Claudio Giuseppe Giacomazzi; Silvia Carla Maria Magnani; Roberto Imparato; Annie Cometto; Adriano Casulli; Riccardo Orusa; et al. (Pathogens)
Purpose: Dirofilariasis is a zoonotic infectious disease caused by a species belonging to the Dirofilaria genus. Human dirofilariasis cases have increased in Europe in the last few decades. Dogs and wild canids represent the definitive hosts and principal reservoirs of Dirofilaria repens, while mosquito species are biological vectors. Humans act as accidental hosts, and clinical manifestations depend on the location of the worm in the organs or tissues. We described the first case of ocular dirofilariasis in the Aosta Valley region (Italy). Case description: a 62-year-old Italian woman complained of recurrent ocular redness, pain and discomfort, accompanied by itching and foreign body sensation in the right eye. The slit lamp biomicroscopic examination revealed conjunctival congestion on the temporal region of bulbar conjunctiva, and a long whitish vermiform mobile mass was detected under the conjunctiva. The anterior chamber showed no flare or cells in either eye, and the dilated fundus examination was normal. The worm was immediately surgically removed to prevent further migration, and was diagnosed morphologically and molecularly as D. repens. Following surgical removal, the symptoms resolved completely and rapidly, with no recurrence of ocular symptoms recorded during 12-month follow-up visits. Conclusions: Ocular dirofilariasis can lead to misdiagnosis due to its rare ocular manifestations, and it is considered an emergent zoonosis in European countries. Accurate diagnosis and control of ocular dirofilariasis by D. repens require a multidisciplinary approach under the One Health framework to effectively address this emergent zoonosis.